Simplified Approach for the Extraction of Quinclorac From Soils - Wang, Yan-Hui; Li, Xin; Zhou, Xiao-Mao; Bai, Lian-Yang (Asian Journal of Chemistry, 2012)
A simplified version of the QuEChERS method for the extraction of quinclorac from soil samples was proposed. Optimum results were obtained dispersing soil in water, followed by the addition of 1 % acetic acid in acetonitrile, magnesium sulfate and sodium acetate as a modification of the quick, easy, cheap, effective, rugged and safe (QuEChERS) method. Liquid chromatography/ ultraviolet (LC-UV) detector was then used to analyze the extracts without any other sample pretreatment. The result showed the recovery ranged from 73.8 to 106.4 % and 66.6 to 87.3 % with the relative standard deviations of 1.9 to 15.7 % and 4.7 to 9.3 % in two soil samples, respectively. The limit of detection (LOD) of the method was 0.05 mg kg-1. The limit of quantification (LOQ) was 0.5 mg kg-1. The half life period of quinclorac was 65.7 and 36.5 days in soil of Changsha and Nanning in China, respectively.